PRIMARY EDUCATION IN LAGOS STATE: IDENTIFYING THE GAPS IN SERVICE DELIVERY - ADEBAYO O. ADEDEJI (International Studies Journal)
Education is a valuable social asset that generates a plethora of externalities that permeate all aspects of society. Consequently, governments must ensure the efficient and effective provision of education as a public service. To achieve this, appropriate structures and management processes must be put in place to meet the educational needs of citizens. This study examines the delivery of primary education in Lagos before and after 1999, utilizing a historical approach to trace the evolution of structures and processes established for primary education delivery. Additionally, quantitative secondary data is employed to evaluate primary education outcomes in the state. While the state has made significant progress, the insufficient collaboration with local government councils and inequitable distribution of primary education facilities have impeded intended outcomes, as evidenced by overcrowded classrooms and a high number of out-of-school children. Delegating some responsibilities to local government councils would promote better collaboration between the state and local governments, and reallocating resources to areas with inadequate educational facilities would enhance educational outcomes.